SISTEM OTOMATISASI RECONNAISSANCE MENGGUNAKAN MODEL OSINT UNTUK MENINGKATKAN KEAMANAN SISTEM INFORMASI PADA UNIVERSITAS MUHAMMADIYAH MAKASSAR - Muh. Fikri Haekal; Muhammad Faisal; Muhyiddin A.M. Hayat (Nusantara Hasana Journal, 2026)
The development of digital technology provides opportunities to develop more interactive learning media through the integration of cybersecurity systems. However, applications that integrate automated reconnaissance with Open-Source Intelligence (OSINT) models are still challenging to implement, especially in terms of system integration and device limitations. This study aims to develop an automated reconnaissance system based on OSINT to identify exposed digital assets at Muhammadiyah University of Makassar. The application was developed using Python and Flask framework, with various OSINT modules integrated including WHOIS lookup, DNS analysis, port scanning, subdomain enumeration, vulnerability scanning, social OSINT, dark web intelligence, and Google dorking. The system was evaluated using Black Box Testing and functional testing methods. Black Box Testing results showed that most main functions operated according to designed scenarios, although several functions were partially successful due to OCR image quality and system integration limitations. The developed application can function as proactive security monitoring media for universities, providing essential technical instruments for IT administrators to map potential data breaches early, enabling proactive mitigation steps and strengthening information system security posture.